Produksi Pigmen Kapang Monascus sp. dari Angkak pada Substrat Tongkol Jagung (Zea mays) dengan Variasi Ukuran Substrat dan Kadar Air - Sesaria Esa Sekar Ardini; Agung Suprihadi; MG Isworo Rukmi (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2014)
Natural dyes in food industry is more demand so its pushes eforts for developing the production. Monascus is one of fungi that is potentially used for anka production that used in industrial products such as meat, fish, soy sauce, and liquor. The aim of this study was to produce pigment from Monascus using corncob with 35 mesh (<0,5 mm), 18 mesh (0,6-1 mm), 10 mesh (1,1-2 mm) particle size substrate and 20%, 40%, 60% moisture content. The production of Monascus sp. pigments made of solid-state fermentation and incubated for 14 days. The parameters observed were pigment production and biomass. Analysis of pigment using spektrophotometer with wavelength (λ) of 500 nm as well as biomass analysis by measuring N-acetyl glucosamin. The results of analysis showed that particle with size 0,6-1 mm from the substrates and with 20% and 40% moisture content was the best condition in process of pigment production using corncob substrate. The production of pigment from fungi with substrate with size 18 mesh ((0,6-1 mm) in 20% moisture content reached 1,1 CVU (Color Value Unit)/ml, and in 40% moisture content reached 1,07 CVU/ml. The highest biomass was reached on 10 mesh (1,1-2 mm) particle size at 20% moisture content reached 0,83 A (absorbance)/gds (gram dry substrates), 40% reached 0,72 A/gds, and 60% reached 0,81 A/gds.Keywords: Solid-state fermentation, corncob, Monascus sp., particle size, moisture content